2018
DOI: 10.18203/2320-6012.ijrms20180618
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of Fournier’s gangrene and use of honey dressing in treatment

Abstract: Genitals and perineal regions are more prone for infection as their tendency to responds to inflammation by causing ABSTRACT Background: Fournier's gangrene is necrotizing fasciitis involving genitals and perineal regions. Fournier's gangrene is a surgical emergency. If not treated immediately it spreads rapidly causing septicemia leading to death. Mainstay of treatment is surgical and regular dressing. Various dressing materials are available like eusol, in our study we use Honey as dressing material. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Mean days the patient was hospitalized were 15.44±6.9 days in EUSOL dressing patients and 15.41±8.41 days in honey dressing patients. There was no significant difference found on comparison of these parameters between two groups 5 . Another study reported the duration of hospital stay to be significantly shorter in honey treated group than that of EUSOL treated group i.e.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Mean days the patient was hospitalized were 15.44±6.9 days in EUSOL dressing patients and 15.41±8.41 days in honey dressing patients. There was no significant difference found on comparison of these parameters between two groups 5 . Another study reported the duration of hospital stay to be significantly shorter in honey treated group than that of EUSOL treated group i.e.…”
Section: Discussionmentioning
confidence: 62%
“…All patients had scrotal involvement followed by scrotal and penis together being involved. On culture report of pus, E.Coli (42.5%) were isolated from majority of samples, Klebsiella Pneumoniae (12.5%) and Pseudomonas (7.5%) were found in few patients 5 5 . In another study, the mean age of Fournier's gangrene patients was noted to be 47±15.8 years 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor personal hygiene is another predisposing factor, but it is not studied in our study. Poor hygiene acts as a source of microbial entry after itching and scratches [ 11 ].…”
Section: Discussionmentioning
confidence: 99%